High content screening of a kinase-focused library reveals compounds broadly-active against dengue viruses. - Deu John M Cruz; Andrea Cristine Koishi; Juliana Bosso Taniguchi; Xiaolan Li; Rafaela Milan Bonotto; Joo Hwan No; Keum Hyun Kim; Sungmin Baek; Hee Young Kim; Marc Peter Windisch; Ana Luiza Pamplona Mosimann; Luana de Borba; et al. (Public Library of Science (PLoS), 2013)
Dengue virus is a mosquito-borne flavivirus that has a large impact in global health. It is considered as one of the medically important arboviruses, and developing a preventive or therapeutic solution remains a top priority in the medical and scientific community. Drug discovery programs for potential dengue antivirals have increased dramatically over the last decade, largely in part to the introduction of high-throughput assays. In this study, we have developed an image-based dengue high-throughput/high-content assay (HT/HCA) using an innovative computer vision approach to screen a kinase-focused library for anti-dengue compounds. Using this dengue HT/HCA, we identified a group of compounds with a 4-(1-aminoethyl)-N-methylthiazol-2-amine as a common core structure that inhibits dengue viral infection in a human liver-derived cell line (Huh-7.5 cells). Compounds CND1201, CND1203 and CND1243 exhibited strong antiviral activities against all four dengue serotypes. Plaque reduction and time-of-addition assays suggests that these compounds interfere with the late stage of viral infection cycle. These findings demonstrate that our image-based dengue HT/HCA is a reliable tool that can be used to screen various chemical libraries for potential dengue antiviral candidates.